Association between irritability and bias in attention orienting to threat in children and adolescents. (26th October 2016) - Salum, Giovanni A.; Mogg, Karin; Bradley, Brendan P.; Stringaris, Argyris; Gadelha, Ary; Pan, Pedro M.; Rohde, Luis A.; Polanczyk, Guilherme V.; Manfro, Gisele G.; Pine, Daniel S.; Leibenluft, Ellen
Abstract : Background: Irritability, a frequent complaint in children with psychiatric disorders, reflects increased predisposition to anger. Preliminary work in pediatric clinical samples links irritability to attention bias to threat, and the current study examines this association in a large population‐based sample. Methods: We studied 1, 872 children (ages 6–14) using the Development and Well‐Being Assessment (DAWBA), Childhood Behavior Checklist (CBCL), and dot‐probe tasks. Irritability was defined using CBCL items that assessed temper tantrums and hot temper. The dot‐probe task assessed attention biases for threat‐related (angry face) stimuli. Multiple regression analysis was used to assess specificity of associations to irritability when adjusting for demographic variables and co‐occurring psychiatric traits. Propensity score matching analysis was used to increase causal inference when matching for demographic variables and co‐occurring psychiatric traits. Results: Irritability was associated with increased attention bias toward threat‐related cues. Multiple regression analysis suggests associations between irritability and threat bias are independent from demographic variables, anxiety, and externalizing traits (attention‐deficit/hyperactivity, conduct, and headstrong/hurtful), but not from broad internalizing symptoms. Propensity score matching analysis indicated that this association was found for irritable versus nonirritable groups matched on demographic and co‐occurring traits including internalizing symptoms. Conclusions: Irritability in children is associated with biased attention toward threatening information. This finding, if replicated, warrants further investigation to examine the extent to which it contributes to chronic irritability and to explore possible treatment implications.